Analisis Beban Kerja, Stres Kerja dan Lingkungan Kerja Terhadap Kinerja Guru Yayasan Bina Agung - Marsela, Grace; Pratama , Siswa; Wakhyuni, Emi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine how workload, occupational stress, and the work environment contribute to the performance of teachers at Yayasan Sekolah Bina Agung Medan. A quantitative associative method was applied, utilizing questionnaires distributed to 35 tenured teachers. Data analysis involved tests for validity and reliability, classical assumption analysis, and multiple linear regression using SPSS version 31, including t-tests, F-tests, and determination coefficient. The findings revealed that workload had a significant and positive partial influence on teacher performance. In contrast, job stress and the work environment did not have a significant effect when assessed individually. Nevertheless, when analyzed together, the three variables collectively had a meaningful impact on performance outcomes. The determination coefficient (R²) value was 0.881, indicating that 88.1% of the variation in teacher performance could be explained by these factors. These results emphasize the critical role of managing workload efficiently while acknowledging the supportive role of stress and environmental conditions in fostering teacher effectiveness.